Cationization of Eucalyptus wood waste pulps with diverse lignin contents for potential application in colored wastewater treatment. Issue 60 (29th October 2019) - Grenda, Kinga; Gamelas, José A. F.; Arnold, Julien; Cayre, Olivier J.; Rasteiro, Maria G.
Abstract : Eucalyptus wood waste has been used to produce cationic lignocellulose-based polyelectrolytes (PELs) and the new PELs proved to be efficient flocculants in the decoloration of dye-containing waters with potential application in several industries. Abstract : Modification of cellulosic-rich materials such as Eucalyptus wood waste and production of cellulose-based polyelectrolytes (PELs) presents several advantages for a variety of applications, when compared to the utilization of synthetic PELs, due to the nature, availability, high biodegradability and low or no toxicity of cellulosic materials. Moreover, valorization of the cellulosic waste itself to provide end products with higher added value is also an important aspect. In the present work, the objective was to evaluate the possibility of cationizing more complex and heterogeneous chemical pulps, obtained from Eucalyptus wood waste, with different cellulose purity and a relatively high lignin content (up to 4.5%). A two-step reaction (with sodium periodate and Girard's reagent T) was employed and a range of cellulose-based cationic polyelectrolytes were produced with different degrees of substitution. The final products were characterized by several analytical techniques and the bio-PELs with the highest and the lowest substitution degree by cationic groups were evaluated in a new application, as flocculants in the decoloration of model effluents, bentonite having been used as an inorganic aid. Also, possible mechanisms of flocculation were discussed and the results compared with those of a synthetic flocculant, often used in these treatments, cationic polyacrylamide. Lignocellulosic-PELs proved to be very favorable eco-friendly flocculation agents for the decoloration of dye-containing waters with potential application in several industries.